Chicago classification v4.0 protocol improves specificity and accuracy of diagnosis of oesophagogastric junction outflow obstruction. Issue 4 (25th June 2022) - Visaggi, Pierfrancesco; Ghisa, Matteo; Del Corso, Giulio; Baiano Svizzero, Federica; Mariani, Lucia; Tolone, Salvatore; Frazzoni, Marzio; Buda, Andrea; Bellini, Massimo; Savarino, Vincenzo; Penagini, Roberto; Gyawali, C. Prakash; et al.
Summary: Background: Chicago classification version 4.0 (CCv4.0) introduced stringent diagnostic criteria for oesophagogastric junction outflow obstruction (EGJOO), in order to increase the clinical relevance of the diagnosis, although this has not yet been demonstrated. Aims: To determine the prevalence of EGJOO using CCv4.0 criteria in patients with CCv3.0‐based EGJOO, and to assess if provocative manoeuvres can predict a conclusive CCv4.0 diagnosis of EGJOO. Methods: Clinical presentation, high resolution manometry (HRM) with rapid drink challenge (RDC), and timed barium oesophagogram (TBE) data were extracted for patients diagnosed with EGJOO as per CCv3.0 between 2018 and 2020. Patients were then re‐classified according to CCv4.0 criteria, using clinically relevant symptoms (dysphagia and/or chest pain), and abnormal barium emptying at 5 min on TBE. Receiver operating characteristic (ROC) analyses identified HRM predictors of EGJOO. Results: Of 2010 HRM studies, 144 (7.2%) fulfilled CCv3.0 criteria for EGJOO (median age 61 years, 56.9% female). Upon applying CCv4.0 criteria, EGJOO prevalence decreased to 1.2%. On ROC analysis, integrated relaxation pressure during RDC (RDC‐IRP) was a significant predictor of a conclusive EGJOO diagnosis by CCv4.0 criteria (area under the curve: 96.1%). The optimal RDC‐IRP threshold of 16.7 mm Hg had 87% sensitivity, 97.1% specificity, 95.7% negative predictive value and 91.3% positive predictive value for a conclusive EGJOO diagnosis; lower thresholds (10 mmHg, 12 mmHg) had better sensitivity but lower specificity. Conclusion: CCv4.0 criteria reduced the prevalence of EGJOO by 80%, thereby refining the diagnosis and identifying clinically relevant outflow obstruction. Elevated RDC‐IRP can predict conclusive EGJOO per CCv4.0. Abstract : Prevalence and predictors of esophagogastric junction outflow obstruction according to chicago classification v4.0.